Explaining the Causal Relationships Between Childhood Maltreatment and Attachment Styles with Forgiveness in Betrayal Victims: The Mediating Role of Defensive Mechanisms - Mahmoudvand, Mohsen; Zahrakar, Kianoush; Hasani, Jafar (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  The primary aim of the current research was to present a forgiveness model based on childhood maltreatment and attachment styles with the mediating role of defensive mechanisms in betrayal victims.Methods and Materials: The method of this study was descriptive-correlational and of the structural equation modeling type. The population of this study consisted of individuals who were victims of betrayal and had sought counseling in Tehran in the year 2022, from whom 653 persons were selected through convenience sampling. The instruments used in this study were the Childhood Trauma Questionnaire by Bernstein et al. (2003), the Attachment Styles Questionnaire by Hazan and Shaver (1987), the Defense Mechanisms Questionnaire by Andrews et al. (1993), and the Forgiveness Questionnaire by Rey et al. (2001). Data were analyzed using SPSS-25 and AMOS-24 software.Findings: The results indicated that there is a negative relationship between childhood maltreatment, insecure attachment styles, and undeveloped and neurotic defensive mechanisms with forgiveness (P